2006
DOI: 10.1002/bit.20808
|View full text |Cite
|
Sign up to set email alerts
|

Novel reporter gene in a fluorescent‐based whole cell sensing system

Abstract: A common problem encountered when using fluorescence detection in real samples analysis is that the matrix may contain compounds that autofluorescence or that can be excited at the wavelengths of commonly employed fluorescent reporter molecules. This causes an increase in background fluorescence, which in turn tends to compromise the detection limits of the system. To address this issue, we investigated the use of a reporter enzyme that produces fluorescent compounds, which can be excited at wavelengths that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The maximum absorption at 410 nm was examined for cells expressing UMT fused to ALAS or UROD. Expression of the GLTR, CPOX, or SCFC partner resulted in a minor absorption peak at 375 nm and major one at 350 nm, which represent sirohydrochrolin and trimethylpyrrocorphin respectively (Feliciano et al, 2006), similar to that of MBP-UMT (Fig. 6B).…”
Section: Effects Of the Five Enzymes On The Umt Reportermentioning
confidence: 85%
See 3 more Smart Citations
“…The maximum absorption at 410 nm was examined for cells expressing UMT fused to ALAS or UROD. Expression of the GLTR, CPOX, or SCFC partner resulted in a minor absorption peak at 375 nm and major one at 350 nm, which represent sirohydrochrolin and trimethylpyrrocorphin respectively (Feliciano et al, 2006), similar to that of MBP-UMT (Fig. 6B).…”
Section: Effects Of the Five Enzymes On The Umt Reportermentioning
confidence: 85%
“…Additional ALA can increase cell fluorescence in the UMT reporter system (Feliciano et al, 2006;Roessner, 2002), resulted from the transformation of ALA into Uro'gen III in E. coli by the chromosome-encoded enzymes. In the current study, we identified that the supplementary ALA declined sensitivity of UMT as the solubility reporter for monitoring TEVp variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24) When this occurs, an excess of UPMTase also catalyzes a third methylation of uroporphyrinogen III at position 12 to give an overmethylated trimethylpyrrocorphin, which has no obvious physiological role. 13,25) These two products, sirohydrochrolin and trimethylpyrrocorphin, are known to emit strong red fluorescence when illuminated by UV, and their spectra patterns are in good agreement with those observed in cell extracts of E. coli JM109/pRF1.5 (Fig.…”
Section: Analysis Of Fluorescent Metabolites In E Coli Transformant mentioning
confidence: 99%